High-efficiency CRISPR gene editing in C. elegans using Cas9 integrated into the genome - Matthew L. Schwartz (Public Library of Science (PLoS), 2021)
Gene editing in C. elegans using plasmid-based CRISPR reagents requires microinjection of many animals to produce a single edit. Germline silencing of plasmid-borne Cas9 is a major cause of inefficient editing. Here, we present a set of C. elegans strains that constitutively express Cas9 in the germline from an integrated transgene. These strains markedly improve the success rate for plasmid-based CRISPR edits. For simple, short homology arm GFP insertions, 50–100% of injected animals typically produce edited progeny, depending on the target locus. Template-guided editing from an extrachromosomal array is maintained over multiple generations. We have built strains with the Cas9 transgene on multiple chromosomes. Additionally, each Cas9 locus also contains a heatshock-driven Cre recombinase for selectable marker removal and a bright fluorescence marker for easy outcrossing. These integrated Cas9 strains greatly reduce the workload for producing individual genome edits. Author summary Germlines have evolved specialized mechanisms to protect themselves from invasions by transposons and viruses, which create barriers to genome editing techniques. For example, transgenes are silenced in the germline of the nematode C. elegans, thereby creating a barrier to CRISPR editing by Cas9. To facilitate gene editing, we built a collection of C. elegans strains in which Cas9 is never silenced. CRISPR is significantly more efficient in these animals, decreasing the effort researchers need to expend to get edited animals. The strains are available in multiple genetic backgrounds, and contain accessory transgenes to simplify downstream genetics. Together, these strains enable efficient, low-cost genome editing in C. elegans.